ALASAN G7 MENUNDA KEANGGOTAAN RUSIA DALAM G8 SEBAGAI RESPON TERHADAP ANEKSASI CRIMEA TAHUN 2014 - Bimo Satryo Wibowo (HI 16 UMY 111, 2016)
Ukraine crisis had begun in November 2013 followed by Russia’s annexation over Crimea. It had caused internationally sanctioned upon Russia. The action has been claimed as a violation towards International Law which related to territory and sovereignty. Group of Eight (G8), as one of organization in which Russia had registered in, also taking action with suspending Russia’s membership. This paper will explain more the reason behind G7’s policy which suspends Russia’s policy under the role of G7 as international organization and international law perspective. Keywords Rusia, Crimea, Ukraina, Group of Seven, Group of Eight, Hukum Internasional, Organisasi Internasional